Analysis of Students' Thinking Structures Regarding Personality Types in Solving Mathematical Problems Through Defragmentation - Hadi, Heri Sopian; Irhas, Irhas; Assa'ady, M. Chothibul Umam; Azhari, Haerulddin; Akbar, Lalu Ajimuliardi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The extrovert-introvert personality type has different energy sources for the individual, which affects the difference in thinking structures that will be obtained in solving problems. The thinking structure is the internal representation of students' mental activities that describes the flow of solving mathematical problems. Therefore, the mistakes made by students in solving mathematical problems require proper resolution, one of which is defragmentation. The purpose of this research is to analyze students' thinking structures related to personality types in solving problems through defragmentation. The approach used in this research is qualitative with a descriptive research type. Subject selection was carried out using purposive sampling technique with criteria being students who have extrovert-introvert personality types regarding mistakes in understanding and transformation. The research data consisted of answers, recordings of semi-structured interviews, and students' think-aloud results. The analysis techniques used are data reduction, data presentation, and conclusion drawing. The results show that defragmentation can help students with extrovert-introvert personality types to understand mistakes and perform transformations to reorganize their thinking structure. This is evidenced by the completeness of students' thinking structures from the stages of reading, understanding, transforming, analyzing, and evaluating.